PEMANFAATAN KALCER ( Kamis Literasi Numerasi Ceria) UNTUK PENGUATAN LITERASI SISWA SEKOLAH DASAR - Sulastri Sulastri; Hairatul Adwiah; Nuralmujadillah; Khafizah Aulia; Dwi Damayanti Putri; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to implement the Kamis Literasi Numerasi Ceria (KALCER) program as an innovative approach to improving the basic literacy skills of elementary school students through a word-based educational game. The program focuses on developing the ability to form words, read, and write in a fun and interactive manner. This research employs the Classroom Action Research (CAR) method to assess the impact of this program within a single class session. Quantitative data were collected through a simple literacy test conducted before and after the game. Additionally, student attitudes, motivation, and perceptions during the literacy activity were assessed through direct observation. The results indicate that the implementation of KALCER successfully enhanced student engagement in literacy activities, word-forming skills, and writing quality on the whiteboard. The challenges identified were related to classroom management, particularly with students who were difficult to control. Overall, the program proved effective in enhancing student literacy and can serve as an innovative learning model in elementary schools.